1999
DOI: 10.1177/074873099129000489
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic Control of the Rat Pineal Arylalkylamine-N-Acetyltransferase and Hydroxyindole-O-Methyltransferase Gene Expression and Its Effect on Melatonin Synthesis

Abstract: Photoperiodic changes of pineal melatonin (MEL) profile are accompanied by parallel changes of arylalkylamine-N-acetyltransferase (AA-NAT) activity. In the present study, the authors investigated, for the first time, whether two other important variables of pineal metabolism, AA-NAT and hydroxyindole-O-methyltransferase (HIOMT) gene expression, also may be affected by the photoperiod. Evening rises in AA-NAT and HIOMT mRNA and in circulating MEL occurred concomitantly with an increased delay from dark onset as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
8

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 46 publications
4
45
0
8
Order By: Relevance
“…It is possible that small amounts of N-acetylserotonin produced by other transferases are methylated by residual pineal HIOMT enzyme. The rhythm could then come from a low-amplitude rhythm in pineal HIOMT activity similar to the rhythm reported in rats (29). It should be pointed out that very low levels of pineal melatonin synthesis have also been reported elsewhere in C57Bl mice (33,35).…”
Section: Discussionsupporting
confidence: 67%
“…It is possible that small amounts of N-acetylserotonin produced by other transferases are methylated by residual pineal HIOMT enzyme. The rhythm could then come from a low-amplitude rhythm in pineal HIOMT activity similar to the rhythm reported in rats (29). It should be pointed out that very low levels of pineal melatonin synthesis have also been reported elsewhere in C57Bl mice (33,35).…”
Section: Discussionsupporting
confidence: 67%
“…We are currently investigating the neurotransmitters and mechanisms implicated in this regulation. In the rat, the photoperiodic variation in HIOMT activity is positively correlated with the rate of Hiomt gene transcription, thus suggesting an involvement of the NAergic stimulation (Ribelayga et al, 1999a). In the pineal gland of the European hamster, the increase in HIOMT activity is associated with a large increase in the number of NPYergic fibers but not in TH-positive fibers from the end of October to mid-December .…”
Section: Multiple Regulation Of Pineal Melatonin Synthesis In Mammalsmentioning
confidence: 91%
“…In vivo, in the rat, we have observed that the duration of the nocturnal peak of Hiomt mRNA is longer under SP (8L/16D) than under LP (16L/8D). The SP increase in Hiomt gene expression led to a significant increase (30 to 40%) in mean HIOMT activity throughout 24 h, probably related to an augmentation of protein synthesis (Ribelayga et al, 1999a;Fig. 6).…”
Section: Multiple Regulation Of Pineal Melatonin Synthesis In Mammalsmentioning
confidence: 95%
See 1 more Smart Citation
“…O passo final da produção ocorre quando a enzima hidroxindole-O-metiltransferase (HIOMT) converte a NAS em melatonina 10 . A atividade da HIOMT no período noturno apresenta um aumento de 1,5 vez, enquanto o seu RNAm tem um aumento de 2 vezes (17,18).…”
Section: A Molécula De Melatoninaunclassified